Otimização estrutural em problemas dinâmicos - Lira, Aécio (1978)
Presents an optimization structural procedure under dynamic constraints. The constraints imposed on the optimization problem can be subdivided into two classes: constraint on the natural frequency of the structure and dynamic response constraint. It is presented a general computer program for the truss element under harmonic excitation to make the following analysis: a) static analysis b) natural frequencies e) dynami e response (P = Pₑ ⁱᵚᵗ) d) dynami e response optimization (P = Pₑⁱᵚᵗ) e) frequency optimization.